Thinking Dangerously: The Role of Higher Education in Authoritarian Times - Giroux, Henry A. (Chowanna, 2020)
The notion of a neutral, objective education is an oxymoron. Education and pedagogy do not exist outside of ideology, values and politics. Ethics, when it comes to education, demand an openness to the other, a willingness to engage a “politics of possibility” through a continual critical engagement with texts, images, events and other registers of meaning as they are transformed into pedagogical practices both within and outside of the classroom. Education is never innocent: It is always implicated in relations of power and specific visions of the present and future. This suggests the need for educators to rethink the cultural and ideological baggage they bring to each educational encounter. It also highlights the necessity of making educators ethically and politically accountable for and self-reflective about the stories they produce, the claims they make upon public memory, and the images of the future they deem legitimate.